Desa Toabo Sebagai Model Moderasi Beragama Dalam Konteks Masyarakat Multikultural - Tahir, Bakri; Heriamsal, Krisman (Jurnal SUARGA: Studi Keberagamaan dan Keberagaman, 2025)
Religious diversity in Indonesia is often challenged by the potential for conflict based on ethnic, religious, racial, and intergroup differences (commonly referred to as SARA). However, amid frequent incidents rooted in such tensions, the village of Toabo in Mamuju Regency, West Sulawesi, stands out as a success story in maintaining social harmony. This has been achieved through its effective implementation of religious moderation within a diverse community. This study examines the key factors that have contributed to the success and sustainability of Toabo as a Village of Religious Moderation. Employing a qualitative analytical case study approach, data were collected through literature review and interviews with local residents, religious leaders, and government officials. The findings reveal that the availability of worship facilities for all religious groups, interfaith participation in social and religious activities, the active roles of religious leaders and village authorities in fostering harmonious relations, equitable distribution of power, and the integration of religious moderation values into the school curriculum are among the critical factors contributing to Toabo's success and sustainability as a model of religiously moderate community living.